Yoga in Transformation Historical and Contemporary Perspectives - Baier, Karl; Maas, Philipp André; Preisendanz, Karin (2018)
This volume explores aspects of yoga over a period of about 2500 years. In its first part, it investigates facets of the South Asian and Tibetan traditions of yoga, such as the evolution of posture practice, the relationship between yoga and sex, yoga in the theistic context, the influence of Buddhism on early yoga, and the encounter of Islam with classical yoga. The second part addresses aspects of modern globalised yoga and its historical formation, as for example the emergence of yoga in Viennese occultism, the integration of yoga and nature cure in modern India, the eventisation of yoga in a global setting, and the development of Patañjali's iconography. In keeping with the current trend in yoga studies, the emphasis of the volume is on the practice of yoga and its theoretical underpinnings.